Combining ability analysis for seed yield and component traits in Indian mustard [Brassica juncea (L.) Czern & Coss.] - Gideon J. Synrem*, N. R. Rangare, Anil K. Choudhari, Sujeet Kumar and Ibadaiahun Myrthong (Electronic Journal of Plant Breeding, 2015)
Combining ability of eight quantitative traits was studied in 12 lines, 4 testers and 48 F1’s in Line x Tester mating design to know the inheritance pattern of yield attributes of Indian mustard [Brassica juncea (L.) Czern & Coss]. The estimates of gca and sca variances showed the preponderance of non-additive gene action for all the traits studied. Data revealed that variances due Line x Tester effect were significant for seed yield and all the traits studied. Among the lines and testers, good general combining parents BASANTI, CS 54, VARUNA, DURGAMANI, GM 1 and PM 67 exhibited desirable negative and highly significant gca effect for days to 50% flowering and days to maturity and the parents RL-1359, KRISHNA, RH-819 and JM-2 were good general combiners as they showed positive and highly significant gca effect for seed yield plant-1, plant height, primary branches plant-1, secondary branches plant-1, number of seeds siliqua-1, length of siliqua and days to maturity indicating the presence of additive gene action or additive x additive interaction effects. Hybrids RL 1359 x JM 2, KRISHNA x JM 2, GM 2 x JM 2 and CS 54 X LAXMI exhibited significant and positive specific combining ability effects for seed yield plant-1, days to 50 % flowering, secondary branches plant-1 and number of seeds siliqua-1. However, on the basis of per se performance and significant specific combining ability effect for seed yield plant-1 hybrids RL 1359 x JM 2 and KRISHNA x JM 2 were considered to be most promising for further exploitation in breeding programme.